2015
DOI: 10.1016/j.actaastro.2015.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Solar sail Lyapunov and Halo orbits in the Earth–Moon three-body problem

Abstract: Solar sailing has been proposed for a range of novel space applications, including hovering above the ecliptic for high-latitude observations of the Earth and monitoring the Sun from a sub-L 1 position for space weather forecasting. These applications, and many others, are all defined in the Sun-Earth threebody problem, while little research has been conducted to investigate the potential of solar sailing in the Earth-Moon three-body problem. This paper therefore aims to find solar sail periodic orbits in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Many works in the literature (e.g., References [22][23][24][26][27][28]) describe methods to find solar sail periodic (halo) orbits under the dynamics described in Eq. (11) or similar systems.…”
Section: B Solar Sail Halo Orbitsmentioning
confidence: 99%
“…Many works in the literature (e.g., References [22][23][24][26][27][28]) describe methods to find solar sail periodic (halo) orbits under the dynamics described in Eq. (11) or similar systems.…”
Section: B Solar Sail Halo Orbitsmentioning
confidence: 99%
“…Besides adding an additional family of solar sail orbits to previous work, see Reference [13,14], this paper also investigates, for the first time, the effect of higher-fidelity dynamics on the existence and properties of the solar sail periodic orbits presented. While previous work assumed that the ecliptic and Earth-Moon planes coincide and neglected the lunar eccentricity, this paper accounts for these effects, providing realistic solar sail trajectories by expanding the differential correction technique to a multiple shooting differential correction method.…”
Section: Introductionmentioning
confidence: 99%
“…These orbits can be found through the use of differential correction techniques: by perturbing classical libration point orbits such as Lyapunov, halo, vertical Lyapunov and distant retrograde orbits with a solar sail induced acceleration, entirely new families of orbits result in the Earth-Moon system parametrised by the sail's acceleration [13,14]. Different types of families can be created depending on the steering law assumed for the solar sail.…”
Section: Introductionmentioning
confidence: 99%
“…The results in the linearised system have been transferred to the full non-linear dynamical system (Wawrzyniak and Howell 2011a), but the results presented are limited to one specific steering law and only show one family of orbits at the Earth-Moon L 2 point. Initial results on more extensive families of solar sail periodic orbits in the Earth-Moon system do exist (Heiligers et al 2015), but have been found by solving a two-point boundary value problem, while this paper develops a faster and more accurate differential correction scheme. Furthermore, this paper significantly extends the families found in (Heiligers et al 2015) to Lyapunov, halo, and vertical Lyapunov orbits around both the L 1 and L 2 points as well as Earth-centred and distant retrograde orbits.…”
Section: Introductionmentioning
confidence: 99%
“…Initial results on more extensive families of solar sail periodic orbits in the Earth-Moon system do exist (Heiligers et al 2015), but have been found by solving a two-point boundary value problem, while this paper develops a faster and more accurate differential correction scheme. Furthermore, this paper significantly extends the families found in (Heiligers et al 2015) to Lyapunov, halo, and vertical Lyapunov orbits around both the L 1 and L 2 points as well as Earth-centred and distant retrograde orbits. Finally, this paper investigates for the first time the stability properties of these orbits in order to assess the effect of the solar sail on the orbit stability compared to the classical libration point orbits and the potential need for active orbital control.…”
Section: Introductionmentioning
confidence: 99%